Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1128/jvi.77.1.489-498.2003
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Sequences of Varicella-Zoster Virus Glycoprotein I Targeted by Cellular Transactivating Factors Sp1 and USF Determine Virulence in Skin and T Cells in SCIDhu Mice In Vivo

Abstract: Varicella-zoster virus (VZV) glycoprotein I is dispensable in cell culture but necessary for infection of human skin and T cells in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 43 publications
5
63
0
Order By: Relevance
“…These experiments demonstrated that VZV spreads efficiently between neural cells in vivo, without changing cellular morphology or expression of neural cell proteins, including hNCAM, hGFAP, and ␤-tubulin III. VZV gene expression in neural cells differed dramatically from VZV infection of epidermal and dermal cells in human skin in vivo, which is associated with cell destruction and release of infectious virions (20)(21)(22)(23)(24). IE62, the major viral transactivating protein and an important component of the virion tegument (38,39), was restricted to the nuclei of neurons and glial cells, whereas IE62 localized to the cytoplasm of infected skin cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These experiments demonstrated that VZV spreads efficiently between neural cells in vivo, without changing cellular morphology or expression of neural cell proteins, including hNCAM, hGFAP, and ␤-tubulin III. VZV gene expression in neural cells differed dramatically from VZV infection of epidermal and dermal cells in human skin in vivo, which is associated with cell destruction and release of infectious virions (20)(21)(22)(23)(24). IE62, the major viral transactivating protein and an important component of the virion tegument (38,39), was restricted to the nuclei of neurons and glial cells, whereas IE62 localized to the cytoplasm of infected skin cells.…”
Section: Discussionmentioning
confidence: 98%
“…VZV causes lytic infection of human dermal and epidermal cells in skin xenografts in vivo (20)(21)(22)(23)(24)38). To compare VZV protein expression in human neural and skin cells in vivo, skin xenografts were collected 3 weeks after VZV infection, and alternate sections were examined for IE62, IE63, ORF47 kinase, or gE synthesis (Fig.…”
Section: Vzv Protein Expression In Infected Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that promoters of all kinetic classes of VZV genes contain cognate binding sites for a variety of cellular transcription factors, e.g. Oct-1, USF, Sp1, NF-kB and AP-1 (Ito et al, 2003;Kinchington et al, 1994;Meier et al, 1994;Rahaus & Wolff, 2000), which are all targets of upstream signalling pathways. Downregulation of the expression of AP-1 affects the efficiency of transactivation and effectiveness of replication .…”
Section: Discussionmentioning
confidence: 99%
“…10B). Infectious rOKA/ ORF63rev[S185] was not recovered at 20 days, but this pattern was due to extensive infection and depletion of T cells, by immunohistochemistry analysis (data not shown); declining titers at days 21 to 28 days after T-cell infection with low passage clinical isolates or intact recombinants made from cosmids is characteristic of VZV replication in T-cell xenografts (3,13,32,40).…”
Section: Analysis Of Ie62/ie63 Binding In the Ie63 Mutant Virusesmentioning
confidence: 99%